Digital information ecosystems : smart press - Dominique, Augey (Libros electrónicos en Ebscohost, 2019)
Digital information, particularly for online newsgathering and reporting, is an industry fraught with uncertainty and rapid innovation. Digital Information Ecosystems: Smart Press crosses academic knowledge with research by media groups to understand this evolution and analyze the future of the sector, including the imminent employment of bots and artificial intelligence